IDENTIFICATION AND TAXONOMICAL STUDIES OF FRUIT FLIES ON CUCURBITS IN KASHMIR VALLEY - S. A. GANIE; Z. H. KHAN; A. PADDER, SHAMIM (The Bioscan, 2013)
The study was carried out during 2008-2009 at six locations namely Batamaloo, Dal and Shalimar in district Srinagar, Chadoora, Bugam and Narkara in district Budgam. Various cucurbit crops namely cucumber, bottle gourd, ridge gourd and bitter gourd were selected. Four species of fruit flies on cucurbits namely Bactrocera cucurbitae, B. dorsalis, B. tau and B. scutellaris were identified on the basis of taxonomical characters, while B. scutellaris was first time reported from Kashmir valley.